1974
DOI: 10.1126/science.184.4138.793
|View full text |Cite
|
Sign up to set email alerts
|

Radioreceptor Assay of Human Chorionic Gonadotropin: Detection of Early Pregnancy

Abstract: A rapid, sensitive, and specific radioreceptor assay for the determination of human chorionic gonadotropin and luteinizing hormone in plasma is described. Plasma membranes of bovine corpora lutea of early pregnancy, which bind biologically active labeled human chorionic gonadotropin, have been used as receptor. Pregnancy could be detected by assaying the gonadotropin in plasma samples obtained from day 6 to 8 after conception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…hCG (CR-119) showed 1.4% and 9.0% crossreactivity in the homologous RIA for hCGa and hCGf3, respectively. RRA was performed by the method described by Saxena et al (11), using plasma membranes of bovine corpus luteum. The membranes were generously supplied by Wampole Laboratories.…”
Section: Materials and Methods Bacterial Extracts A Microorganism Tementioning
confidence: 99%
“…hCG (CR-119) showed 1.4% and 9.0% crossreactivity in the homologous RIA for hCGa and hCGf3, respectively. RRA was performed by the method described by Saxena et al (11), using plasma membranes of bovine corpus luteum. The membranes were generously supplied by Wampole Laboratories.…”
Section: Materials and Methods Bacterial Extracts A Microorganism Tementioning
confidence: 99%
“…When we attempted to apply the RRA method to the assay of serum samples, nonspecific interference by the serum was a serious problem. Saxena et al (1974) reported a RRA system for measuring the serum LH and hCG using bovine corpora lutea as the receptor preparation, but they mentioned nothing about the nonspecific interference by serum. In our preliminary experiments, a potent nonspecific interference with the binding of 125I-LH to the receptor preparation was demonstrated in the monkey serum, resulting in a flattening of the standard curve.…”
Section: Discussionmentioning
confidence: 99%
“…Human chorionic gonadotropin (choriogonadotropin) (HCG) is a product of trophoblasts and is synthesized at a very early stage of pregnancy, i.e., within [6][7][8] days of the fertilization of the egg (1). It provides a critical support to the corpus luteum, which decays in its absence, resulting in menstruation.…”
mentioning
confidence: 99%